Optimization of Dialogical Patrol by the Samapta Unit to Prevent Theft by Weighting in the Legal Area of Polres Batang Jurisdiction - Maldine, Maldine Ikhtiarsyah Putra (Indonesian Journal of Police Studies, 2024)
The crime of theft by weighting in the jurisdiction of the Batang Police is the dominating list of criminal disturbances. Basically, the Batang Resort Police through the Samapta Unit has a big role to control and prevent cases of theft by weighting preventive efforts through dialogic patrols. Implementation of routine dialogic patrols runs efficiently, but is not fully optimal. This is based on the number of theft crimes by weighting in the Legal Area of ​​the Batang Police which still fluctuates every month. This situation motivated the author to conduct more in-depth research on the Optimization of the Samapta Unit Dialogical Patrol to Prevent Theft by Weighting in the Legal Area of ​​the Batang Police. The research was conducted using a qualitative research approach and case studies. That is, the subjects in this study participated directly in the field. This study uses data collection techniques in the form of observation, interviews, and documentation studies. Through these documents, the data that has been collected is then validated for its correctness through triangulation and determining the data to be used through data reduction, data presentation, and determination of conclusions. The research findings were then examined further, then analyzed using management theory, organizational resource theory, and SWOT analysis theory. The final result of this writing finds that the problem can be answered through the symptoms that occur in the form of dialogic patrol consistency which is assessed based on the Regulation of the Head of the Indonesian National Police and Security Maintenance Agency Number 1 of 2017 concerning patrols. Patrols are an effective preventive effort when viewed from the process. However, maximum results cannot be shown optimally and sustainably. This is influenced by the management of the implementation of dialogic patrols and the organizational resources of patrol personnel so that efforts are needed to optimize dialogic patrols to achieve the desired results.